Phosphate removal and recovery using immobilized phosphate binding proteins - Venkiteshwaran, K. (2021)
The resultant PBP beads were saturated with Pi and exposed to varying pH (pH 4.7 to 12.5) and temperatures (25–45 °C) to induce Pi release. Increase in temperature from 25 to 45 °C and pH conditions between 4.7 and 8.5 released less than 20% of adsorbed Pi. However, 62% and 86% of the adsorbed Pi was released at pH 11.4 and 12.5, respectively. Kinetic experiments showed that Pi desorption occurred nearly instantaneously (<5 min), regardless of pH conditions, which is advantageous for Pi recovery. Additionally, no loss in Pi adsorption or desorption capacity was observed when the PBP beads were exposed to 10 repeated cycles of adsorption/desorption using neutral and high pH (≥12.5) washes, respectively. The highest average Pi adsorption using the PBP beads was 83 ± 5%, with 89 ± 4.1% average desorption using pH 12.5 washes over 10 wash cycles at room temperature. Thermal shift assay of the PBP showed that the protein was structurally stable after 10 cycles, with statistically similar melting temperatures between pH 4 and 12.5. These results indicate that immobilized high-affinity PBP has the potential to be an effective and reversible bio-adsorbent suitable for Pi recovery from water/wastewater.